Cancer Incidence of Child Population of the Russian Federation and its Provision of Medical Care (Doctors, Bedspace, Diagnostic and Therapeutic Technologies): Analysis of Statistical Data for 2013 - M. Yu. Rykov; N. A. Susulyova; O. V. Chumakova; Ye. N. Baybarina; V. G. Polyakov ("Paediatrician" Publishers LLC, 2016)
Background: Cancer is the second most common cause of death in children. The organization of cancer care for children requires further reforming and rational use of available resources.Objective: Our aim was to assess the provision of federal districts (FD) with cancer specialists and relevant bedspace needed for providing medical care for children with newly diagnosed malignant disease.Methods: The ecological study investigated reports of regional ministries and departments of health of 82 subjects of the Russian Federation for 2013. It was analyzed the morbiden (newly diagnosed cases of cancer) of children aged 0-17 years, the provision of bedspace, doctors, diagnostic and therapeutic technologies.Results: In 2013 it was registered 3378 children with cancer. The average incidence rate in Russia amounted to 12.4 per 100 thousand of the child population, in the RF subjects index values ranged from 5.5 to 21.8. 1705 (50.5%) patients were sent to federal clinics. In total, in 2013 in Russia there were 51 children's oncology departments with 2021 beds (including beds in non-core departments), therewith, the provision of bedspace varied by FD from 0.40 to 1.13 per 10 thousand of the child population. Treatment of children with cancer was carried out by 390 doctors, 138 (35.4%) among them did not have a certificate of Pediatric Oncology. The provision of doctors varied by FD from 0.06 to 0.20 per 10 thousand of the child population. The availability of modern diagnostic tools in the RF remains at a relatively low level. As a result, 76.6% of all newly diagnosed cancers were stage III-IV.Conclusion: It is required the improving of the vertical and the amount of specialized medical care for children with newly diagnosed cancer.